Underlying Mechanisms and Potential Therapeutic Molecular Targets in Blood-Brain Barrier Disruption after Subarachnoid Hemorrhage - Li, Yuchen; Wu, Pei; Bihl, Ji C.; Shi, Huaizhang (Current Neuropharmacology, 2020)
Aneurysmal subarachnoid hemorrhage (aSAH) is a subtype of hemorrhagic stroke with significant morbidity and mortality. Aneurysmal bleeding causes elevated intracranial pressure, decreased cerebral blood flow, global cerebral ischemia, brain edema, blood component extravasation, and accumulation of breakdown products. These post-SAH injuries can disrupt the integrity and function of the blood-brain barrier (BBB), and brain tissues are directly exposed to the neurotoxic blood contents and immune cells, which leads to secondary brain injuries including inflammation and oxidative stress, and other cascades. Though the exact mechanisms are not fully clarified, multiple interconnected and/or independent signaling pathways have been reported to be involved in BBB disruption after SAH. In addition, alleviation of BBB disruption through various pathways or chemicals has a neuroprotective effect on SAH. Hence, BBB permeability plays an important role in the pathological course and outcomes of SAH. This review discusses the recent understandings of the underlying mechanisms and potential therapeutic targets in BBB disruption after SAH, emphasizing the dysfunction of tight junctions and endothelial cells in the development of BBB disruption. The emerging molecular targets, including toll-like receptor 4, netrin-1, lipocalin-2, tropomyosin-related kinase receptor B, and receptor tyrosine kinase ErbB4, are also summarized in detail. Finally, we discussed the emerging treatments for BBB disruption after SAH and put forward our perspectives on future research.
Keywords: blood-brain barrier